PENGARUH IKLIM ORGANISASI TERHADAP KINERJA PERSONEL PANGKALAN TNI AU SUPADIO - B31111046, ANDRA (Jurnal Manajemen Update, 2017)
This study aims to determine how the organizational climate influence on the performance Supadio air base personnel. The study used the research methods used in this study is a survey and observation with qualitative and quantitative approaches. Collecting data using primary and secondary data obtained by distributing questionnaires to Supadio air base personnel. The sample in this study using the census sampling, with a sample size of less than 100 people. So that the number of samples is equal to the number of population, so in this study obtained a sample of 80 people who are employees at Supadio air base personnel. Results from the study showed it can be seen that the test results indicate a probability value of 0.000 less than 0.05 (probability <0.05) so that it can be concluded that the organizational climate variables affect the performance of personnel. Keywords: Climate Organization and Personnel Performance